Advances and trends in biotechnological production of natural astaxanthin by Phaffia rhodozyma yeast - Mussagy, Cassamo U. [UNESP]; Pereira, Jorge F. B.; Dufossé, Laurent; Raghavan, Vijaya; Santos-Ebinuma, Valeria C. [UNESP]; Pessoa, Adalberto (Taylor & Francis, 2021)
Astaxanthin (AXT) is a natural xanthophyll with strong antioxidant, anticancer and antimicrobial activities, widely used in the food, feed, pharmaceutical and nutraceutical industries. So far, 95% of the AXT global market is produced by chemical synthesis, but growing customer preferences for natural products are currently changing the market for natural AXT, highlighting the production from microbially-based sources such as the yeast Phaffia rhodozyma. The AXT production by P. rhodozyma has been studied for a long time at a laboratory scale, but its use in industrial-scale processes is still very scarce. The optimization of growing conditions as well as an effective integration of upstream-downstream operations into P. rhodozyma-based AXT processes has not yet been fully achieved. With this critical review, we scrutinized the main approaches for producing AXT using P. rhodozyma strains, highlighting the impact of using conventional and non-conventional procedures for the extraction of AXT from yeast cells. In addition, we also pinpointed research directions, for example, the use of low-cost residues to improve the economic and environmental sustainability of the bioprocess, the use of environmentally/friendly and low-energetic integrative operations for the extraction and purification of AXT, as well as the need of further human clinical trials using yeast-based AXT.
Keywords: Astaxanthin; biotechnological production; carotenoid; extraction techniques; Phaffia rhodozyma; yeast